Regulating wildlife conservation and food safety to prevent human exposure to novel virus - Jingjing Yuan (Taylor & Francis Group, 2020)
Epidemiological investigation suggested that the current outbreak of COVID-19 virus was associated with a seafood market, and COVID-19 has been identified a probable bat origin. Similar to SARS event in 2003, such a zoonotic disease showed an animal-to-person and even more serious person-to-person spread, and posed a significant threat to the global health and socio-economic development. We analyzed the association of both outbreaks with wildlife diet in China and proposed suggestions for regulating wildlife conservation and food safety to prevent human exposure to the novel virus, including increasing social awareness of hazards in eating wild animals, strengthening legislation on eating and trading of wild animals, improving the standards for food safety, and establishing market supervision mechanism. Regulatory intervention is not only critical for China but also for other countries where wildlife hunting is prevalent to prevent from novel virus exposures.